Reassociation kinetics-based approach for partial genome sequencing of the cattle tick, Rhipicephalus (Boophilus) microplus - Guerrero, F.D.; Moolhuijzen, P.; Peterson, D.G.; Bidwell, S.; Caler, E.; Bellgard, M.; Nene, Vishvanath M.; Djikeng, Appolinaire (Springer, 2010)
The size and repetitive nature of the Rhipicephalus microplus genome makes obtaining a full genome sequence fiscally and technically problematic. To selectively obtain gene-enriched regions of this tick's genome, Cot filtration was performed, and Cot-filtered DNA was sequenced via 454 FLX pyrosequencing.